1997
DOI: 10.5547/issn0195-6574-ej-vol18-no3-2
|View full text |Cite
|
Sign up to set email alerts
|

CO2 Emissions Limits: Economic Adjustments and the Distribution of Burdens

Abstract: Policies under consideration within the Climate Convention would impose CO2 controls on only a subset of nations. A model of economic growth and emissions, coupled to an analysis of the climate system, is used to explore the consequences of a sample proposal of this type. The results show how economic burdens are likely to be distributed among nations, how carbon "leakage" may counteract the reductions attained, and how policy costs may be influenced by emissions trading. We explore the sensitivity of results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 86 publications
(48 citation statements)
references
References 12 publications
(3 reference statements)
2
45
0
1
Order By: Relevance
“…Although the complexities of alternative implementation schemes may prevent attainment of the cost savings of an ideal trading regime (Hahn and Stavins, 1999), many studies have shown that the potential for cost reductions is great (e.g., Montgomery, Bernstein, and Rutherford, 1998;Jacoby et al, 1997;OECD, 1992;Ellerman, Jacoby, and Decaux, 1998). The analysis conducted here shows the same result.…”
Section: Emissions Tradingsupporting
confidence: 73%
See 1 more Smart Citation
“…Although the complexities of alternative implementation schemes may prevent attainment of the cost savings of an ideal trading regime (Hahn and Stavins, 1999), many studies have shown that the potential for cost reductions is great (e.g., Montgomery, Bernstein, and Rutherford, 1998;Jacoby et al, 1997;OECD, 1992;Ellerman, Jacoby, and Decaux, 1998). The analysis conducted here shows the same result.…”
Section: Emissions Tradingsupporting
confidence: 73%
“…(Equivalent variation, here denoted EV, is a measure of welfare that shows by how much regional well-being, roughly the level of consumption, changes as a result of a policy intervention.) As seen in previous analyses (Jacoby et al, 1997;Jacoby and Sue Wing, 1999;Kolstad, Light, and Rutherford, 1999), the Kyoto Protocol generates welfare losses across Annex B countries in the range 0.5-2.0%, except for Eastern European countries in transition (EET: countries that have moved or are moving from planned economies/communism to market/democratic economies/ governments), a block of nations that realizes minor short-term welfare gains from its improved comparative advantage in relation to the rest of Annex B. For Non-Annex B, the results show welfare losses in excess of those in Annex B for some regions, such as the Persian Gulf (RME), and net welfare gains for others, such as India (IND).…”
Section: The Reference Case With and Without The Kyoto Protocolsupporting
confidence: 72%
“…The EPPA model is a general equilibrium model of the world economy (9) that has very detailed considerations of all relevant energy, industrial, agricultural, and transportation sectors and uses comprehensive regional data for production, consumption, and trade (SI Text 4). The EPPA model has been used in a wide variety of policy applications (e.g., [11][12][13].…”
Section: Integrated Global System Modelmentioning
confidence: 99%
“…The objective is to provide a portfolio of information that can be further analyzed and aggregated according to the abilities and values of the various participants in climate policy discussions. 9 Second, the development of such a structure is a research task-requiring a focusing of effort and redirection of available resources to climate change impacts and the benefits of emissions mitigation. The overriding priority in meeting these needs is research on the fundamental science of climate change impacts, with a special focus on natural ecosystems, their ability to adapt, and potential damage when they cannot.…”
Section: Research Directionsmentioning
confidence: 99%